Pengaruh terapi murotal Al Qur’an terhadap hemodinamik dan GCS pasien cedera kepala - Widaryati Widaryati (Universitas Aisyiyah Yogyakarta, 2016)
This study is a pre experimentation, with the design of one group pre test - post test. The variables measured were hemodynamic and GCS values before and after the intervention . Intervention in the form of the Qur'an murotal for 30 minutes 3 times a day. The research sample number 12 head injury patients at PKU Muhammadiyah Hospital in Yogyakarta to intervention. Analysis of data using Wilcoxon test, because the data were not normally distributed. GCS variable analysis results obtained significance value of 0.04. While the value of the significance of variable blood pressure systolic, diastolic, respiration and pulse frequency is greater than 0.05. It can be concluded murotal therapy Qur’an affect the value of GCS, but had no effect on systolic and diastolic blood pressure, respiration and pulse frequency.